Case report: Familial glycogen storage disease type IV caused by novel compound heterozygous mutations in a glycogen branching enzyme 1 gene - Li, Yiyang; Tian, Chuan; Huang, Si; Zhang, Weijie; Liutang, Qiuyu; Wang, Yajun; Ma, Guoda; Chen, Riling (Frontiers in Genetics, 2022)
Glycogen storage disease type IV (GSD IV), caused by a mutation in the glycogen branching enzyme 1 (GBE1) gene, is a rare metabolic disorder with an autosomal recessive inheritance that involves the liver, neuromuscular, and cardiac systems. Here, we reported a case of familial GSD IV induced by novel compound heterozygous mutations in GBE1. The proband (at age 1) and her younger brother (at age 10 months) manifested hepatosplenomegaly, liver dysfunction, and growth retardation at onset, followed by progressive disease deterioration to liver cirrhosis with liver failure. During the disease course, the proband presented rare intractable asymptomatic hypoglycemia. The liver pathology was in line with GSD IV. Both cases carried pathogenic compound heterozygous mutations in GBE1 mutations, i.e., a missense mutation (c.271T>A, p. W91R) in exon 2 and a deletion mutation in partial exons 3–7. Both mutations are first reported. The internationally pioneered split-liver transplantation was performed during progression to end-stage liver disease, and the patients had normal liver function and blood glucose after. This study broadens the mutation spectrum of the GBE1 gene and the phenotypic spectrum of GSD IV.